Stabilized multiphysics finite element method with Crank–Nicolson scheme for a poroelasticity model. Issue 4 (31st January 2019) - Ge, Zhihao; He, Yanan; Li, Tingting
Abstract : In the paper, we propose a stabilized multiphysics finite element method with Crank–Nicolson scheme for a poroelasticity model. The method can eliminate the locking phenomenon and reveal the multi‐physical process. The lowest equal order finite element pair is used to reduce the computational cost. Furthermore, the method needs no constraint condition Δ t = O ( h 2 ) and achieves optimal convergent order. Numerical tests are provided to illustrate the optimal accuracy and good performance in eliminating locking phenomenon of the method.